Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada RS Paru Dr M Goenawan Partowidigdo Cisarua Bogor Periode 2016 -2020 - Setiawati, Evi; Afif, Muhamad Nur; Triwidatin, Yuppy (Innovative: Journal Of Social Science Research, 2024)
This research is about Financial Ratio Analysis to Assess Financial Performance at Dr M Goenawan Partowidigdo Lung Hospital Cisarua Bogor 2016-2020 Period. The research design used is descriptive quantitative, with primary and secondary data. The results of this study indicate financial ratios based on PER 36 / PB / 2016, namely the cash ratio, current ratio, receivables collection period ratio, fixed asset turnover ratio, return on fixed assets ratio, equity return ratio, Inventory Turnover Ratio, PNBP Revenue to Operating Costs Ratio, and patient subsidy ratio. In 2016 the total financial ratio score showed 17.5 with good criteria. For 2017 the total financial ratio score was 17 with good criteria, as well as in 2018 obtaining good criteria with a score of 13.1 and in 2019 a score of 13.3 with good criteria. Meanwhile, in 2020 it shows moderate criteria with a score of 12.85.